THE MANAGEMENT OF EDUCATION CENTER PROGRAMS FOR STREET CHILDREN EMPOWERMENT IN A NON-GOVERNMENTAL ORGANISATION (NGO) - Idalia Martha Natalia; Ibnu Syamsi (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2019)
This study aims at revealing (1) the implementation of education center programs in Non- Governmental Organizations (NGO) of Rumah Impian (2) the role of NGO in empowering street children through its education center programs by reviewing their management of planning, organizing, implementation, controlling, (3) the constraints faced by NGO in implementing education center programs and (4) the benefits for the street children after the implementation of its education center program. This research can be categorized as case study using a qualitative approach. The subjects of this study were the head and staff of Rumah Impian as well as the street children who participated in the program.The data collection was conducted by interview, observation and documentation. The analysis technique used the interactive analysis model of Miles & Huberman. The validity of the data was through source triangulation by comparing the data of interview, observation and documentation. The results of this study showed that 1) the implementation of the education center program was conducted with fun learning-based teaching and skills development. 2) The role of Rumah Impian according to its participation level for handling street children can be categorized as education roles. 3) The constraints in implementing the program consists of funding, the parental perceptions for the benefits of education center programs, the limited number of assistants, experts for program evaluation and the limited space. 4) The benefits of the program were improving the knowledge and skills among the street children and risky adolescents and changes in positive parental behavior, which were initially antipathic to education center activities, are now turning to be very enthusiastic in suporting education center activities.